Management of the training process in cross-country orienteering on the basis of typical model characteristics of competitive activity and special preparation of the necessary norms - Voronov, Y. S.; Obvintsev, A. A.; Gurskiy, A. V.; Efremenkov, K. N. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to experimental justification of the methodical management of the training process of young orienteering athletes based on the use of typical model characteristics of competitive activity and special preparation of proper norms.